Comparison of Calculation Methods for Cracking Width of Recycled Aggregate Concrete Beam Under Short-term Loads. Issue 1 (May 2021) - Wang, Yuying; Tang, Jiajun; Zhao, Qingming
Abstract: In order to study the formula for calculating the maximum crack width of recycled aggregate concrete beams under short-term load, four methods of calculating the maximum crack width in the existing literature were compared and analyzed through examples. The results show that Yin Lei's calculation method based on bond-slip theory has smaller error and lower data dispersion. The calculated value of the formula agrees well with the experimental value, which can better meet the requirements of safety, applicability and durability.